Performance evaluation of natural dwarf mutant tomato suitable for vertical gardening - Saha, Swati; Chandrashekar, K; Verma, Raj; Tripathi, Savarni (Indian Journal of Horticulture, 2022)
A dwarf mutant genotype Selection-24 (Seln-24) was identified and stabilized from a segregating population of tomato variety Pusa Gaurav. Performance of Seln-24 was compared with six genotypes of tomato, including parental line for resistance to insect vectors, Tomato leaf curl virus and for different horticultural traits. Seln-24 plants were of compact-miniature type and recorded significantly less height (41.53 cm) compared to parent Pusa Gaurav (134.62cm). Fruits are bullet shaped with bright deep red color. Each fruits weighs around 55g. The fruits are firm with thick pericarp (0.5 cm) with two well filled locules which facilitates good shelf -life. It is highly rich in vitamin C and was found tolerant to whiteflies and leaf curl virus. Due to its compact and dwarf nature, Seln-24 requires minimum staking and training. The line is very useful for vertical gardening or container gardening in multistoried buildings in urban setup.